Environmental Culture and Gendered Consumer Perceptions of Sustainable Beverage Packaging in Indonesia - Maya Putri Utami; Budi Widianarko; Peter Ardhianto (Celt: A Journal of Culture, English Language Teaching and Literature, 2026)
This cultural studies research addresses an environmental issue by examining the role of environmental culture on shaping gendered consumer perceptions regarding sustainable beverage packaging in Indonesia SMEs. This study specifically investigates whether gender has influence on four dimensions of consumer perceptions, including beverage packaging in Indonesian SMEs, particularly four dimensions - Environmental Impact (EI), Price and Willingness to Buy (PRICE), Access, Impact and Future (AIF), as well as Perceived Quality (QUAL). This study draws from Environmental Culture Theory and the Value-Belief-Norm framework to explain the gendered perspectives. There are 384 respondents with random sampling technique from Indonesian consumers as the sample of this research. The data is gathered via online questionnaire and independent sample t-test is used as the main data analysis technique. The finding shows that three of four dimensions are found to have significant differences based on gender. Female respondents are found to have higher willingness to pay for sustainable packaging (PRICE), greater optimism and perception toward access, impact and future (AIF), as well as stronger association for perceived quality and sustainable packaging (QUAL). However, no significant difference is found regarding EI which shows that both male and female respondents have strong awareness regarding environmental benefits of sustainable packaging. Overall, the finding supports the Gendered Environmental Culture perspective where social norms, beliefs, and roles are shaping stronger women’s pro-environmental behavior and perceptions